2023
DOI: 10.3390/jpm13010152
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Alexithymia and Social Media Addiction: Exploring the Role of Dysmorphic Symptoms, Symptoms Interference, and Self-Esteem, Controlling for Age and Gender

Abstract: Given the popularity of social media and the growing presence of these tools in the daily lives of individuals, research about the elements that can be linked to their problematic use appears to be of great importance. The objective of this study was to investigate the factors that may contribute to the levels of social media addiction, by focusing on the role of alexithymia, body image concern, and self-esteem, controlled for age and gender. A sample of 437 social media users (32.5% men, 67.5% women; Mage = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 84 publications
2
7
0
Order By: Relevance
“…Concerning the relationship between love addiction and adult attachment, our results showed that only fearful and preoccupied styles showed significant and positive associations with love addiction. This is in line with earlier evidence showing how fearful and preoccupied attachments are associated with different forms of addiction; these two styles of attachment seem to be more frequent in subjects with substance dependence, such as with heroin [ 19 ], alcohol, tobacco, or waterpipes [ 53 ], as well as problematic smartphone use [ 54 ] and social media addiction [ 23 , 55 ], and sexual addiction [ 56 ]. The preoccupied attachment is characterized by fear that others are unavailable in times of need, and involves an anxious search for love and support and dependence on a desire for commitment in relationship, while fearful attachment is characterized by distrust of others’ intentions, compulsive self-reliance, and the low intensitiy of fewer love experiences [ 18 , 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…Concerning the relationship between love addiction and adult attachment, our results showed that only fearful and preoccupied styles showed significant and positive associations with love addiction. This is in line with earlier evidence showing how fearful and preoccupied attachments are associated with different forms of addiction; these two styles of attachment seem to be more frequent in subjects with substance dependence, such as with heroin [ 19 ], alcohol, tobacco, or waterpipes [ 53 ], as well as problematic smartphone use [ 54 ] and social media addiction [ 23 , 55 ], and sexual addiction [ 56 ]. The preoccupied attachment is characterized by fear that others are unavailable in times of need, and involves an anxious search for love and support and dependence on a desire for commitment in relationship, while fearful attachment is characterized by distrust of others’ intentions, compulsive self-reliance, and the low intensitiy of fewer love experiences [ 18 , 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…The lack of adequate interactive regulation skills in the relationship with the caregiver may affect the ability to mentalize [ 42 ] and transform emotional experiences into complex feelings [ 43 ]: the psychological distress of addicted individuals is not “ encoded in words ” [ 44 ] (p. 206) but is expressed in perceptual–action–affect responses [ 44 , 45 ]. Therefore, the mediating role of alexithymia in a vulnerability system acquires increased meaning, as the difficulty identifying and describing feelings and the tendency to display an externally-oriented thought impair the integration of mental states [ 46 ] and favor the development of addictive disorders [ 22 , 47 , 48 , 49 ]. In parallel, the results of this study also highlighted the impact of complex trauma, which was not identified as a relevant mediating factor among gamblers in the study of Gori and colleagues [ 5 ] but was supported for addiction in general by previous research [ 16 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the research's Hypothesis 2: Negative body image mediates the relationship between social withdrawal and social media addiction. Previous studies indicate that both alexithymia and body image are signi cant predictors of social media addiction [32]. However, the interaction mechanism between alexithymia and negative body image regarding the in uence of social withdrawal on social media addiction remains unclear.…”
Section: Introductionmentioning
confidence: 99%